Peningkatan Literasi Koperasi Pada Himpunan Wanita Penyandang Disabilitas Kota Bengkulu - Bertha Iin Esti Indraswanti; Sunoto; Hutapia (Kreativasi : Journal of Community Empowerment, 2023)
one of the vulnerable groups of people who are socially marginalized, health and economic disparities. This group has a higher probability of economic deprivation than non-disabled people so that these shocks affect the productivity and employment of persons with disabilities. Barriers to mobility and accessibility are the main factors in carrying out economic activities. the special needs experienced by this group are seen as an obstacle both in terms of work effectiveness and efficiency making it difficult to participate in the formal labor market. The HWDI Cooperative is still a business group (pre-cooperative) with all-business cooperative types. The high motivation of the management has not been followed by the motivation of other HWDI members so that the business being carried out is still very small with various other obstacles encountered in managing the cooperative. The low motivation of members (both cooperative members and non-cooperative HWDI members) is due to the lack of understanding and knowledge about cooperatives. Therefore the first step taken is to increase cooperative literacy, an understanding of the importance of cooperatives will increase the motivation of members to join, be involved and actively participate in developing cooperative businesses.